2015
DOI: 10.5312/wjo.v6.i11.927
|View full text |Cite
|
Sign up to set email alerts
|

Posterior shoulder instability in the athletic population: Variations in assessment, clinical outcomes, and return to sport

Abstract: Posterior instability of the shoulder is becoming an increasingly recognized shoulder injury in the athletic population. Diagnostic elements, such as etiology, directionality, and degree of instability are essential factors to assess in the unstable athletic shoulder. Concomitant injuries and associated pathologic lesions continue to be a significant challenge in the surgical management of posterior shoulder instability. Return to sport and previous level of play is ultimately the goal for every committed athl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Results in those series that did examine throwers individually after posterior labral repair revealed a rate of return to play for elite throwers of approximately 30% to 60%. 8 Radkowski et al 28 compared the results of posterior capsular labral repair for posterior instability between throwing and nonthrowing athletes and showed similar results in terms of patient satisfaction. The authors used a variety of surgical techniques and found that throwing athletes were less likely to return to preinjury level sports (55%) as compared with nonthrowing athletes (71%).…”
Section: Discussionmentioning
confidence: 98%
“…Results in those series that did examine throwers individually after posterior labral repair revealed a rate of return to play for elite throwers of approximately 30% to 60%. 8 Radkowski et al 28 compared the results of posterior capsular labral repair for posterior instability between throwing and nonthrowing athletes and showed similar results in terms of patient satisfaction. The authors used a variety of surgical techniques and found that throwing athletes were less likely to return to preinjury level sports (55%) as compared with nonthrowing athletes (71%).…”
Section: Discussionmentioning
confidence: 98%
“…In patients who suffer from higher glenoid retroversion (more than 15°-20°) with intact soft tissue, an open wedge osteotomy may be the treatment of choice. DeLong et al[ 37 ] performed a systematic literature review, stating that posterior glenoid osteotomy does not show any good results in terms of return to pre-injury athletic level[ 22 , 38 ].…”
Section: Shoulder Joint Complex In Posterior Shoulder Dislocationmentioning
confidence: 99%
“…Primary injury mechanisms may include (1) repetitive microtrauma leading to attenuation injuries to the posterior capsule and labrum (most common in the military population); (2) acute, traumatic posterior force resulting in shearing at the chondrolabral junction and subsequent capsulolabral detachment; and (3) insidious onset laxity resulting in stretching of the posterior capsule and passive stabilizers. 10 …”
Section: Pathoanatomymentioning
confidence: 99%